2021
DOI: 10.1525/abt.2021.83.7.436
|View full text |Cite
|
Sign up to set email alerts
|

A Journey from Content to Concept Teaching in a Biology Classroom, in the Context of Blended Learning

Abstract: Conceptual teaching was developed three decades ago as an alternative to conventional teaching approaches. It promised a significant shift in teaching practices across different disciplines and age groups. Traditionally, science subjects in high school tend to be content-heavy. Teaching science, especially biology, is still rooted in teaching methods that facilitate factual understanding and low-road transfer of knowledge. As a result, students’ knowledge remains compartmentalized. Students rarely make connect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Prior research has indicated the importance of active and interactive learning strategies in addressing difficulties related to recalling scientific terms and comprehending concepts (Apodaca et al, 2019;Lufri et al, 2020;Mazowiecki-Kocyk, 2021).…”
Section: Challenges Faced By Students In Biology Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research has indicated the importance of active and interactive learning strategies in addressing difficulties related to recalling scientific terms and comprehending concepts (Apodaca et al, 2019;Lufri et al, 2020;Mazowiecki-Kocyk, 2021).…”
Section: Challenges Faced By Students In Biology Learningmentioning
confidence: 99%
“…Blended learning theories highlight the benefits of integrating face-to-face and online learning (Ariawan et al, 2022;Indrawan, Saskara, et al, 2019;Mahande et al, 2021;Purwasih et al, 2021). This can maximize the advantages of both approaches, such as social interaction in face-to-face learning and flexibility in online learning (Mazowiecki-Kocyk, 2021;Purwasih et al, 2021;Sharma and Sarkar, 2020).…”
Section: Modes Of Biology Learning Experienced By Students In Schoolmentioning
confidence: 99%
“…Blended learning can promote the sustainable development of students' learning ability. Literature [18] addresses the development of teaching biology courses within the past decade and analyzes the barriers associated with the development of innovative teaching methods in the biology classroom. It discusses the combination of blended learning with traditional conceptual teaching techniques to promote the innovation of teaching methods in biology courses and different teaching contexts to enhance students' transfer of biological knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…In today's highly developed "Internet+education", people commonly use mobile network devices, and students' learning styles are quietly changing, and the channels of acquiring knowledge and skills are diversifying, so the new education situation brings new challenges and opportunities to the traditional education model. The emergence of new ideas and technologies has led to the integration of information technology and subject curricula, and in this context, the online + offline hybrid teaching model has emerged [5][6][7]. This new teaching model creates a personalized and interactive learning environment for learners and enables the sharing of educational resources, which not only brings dividends to higher education and basic education, but also benefits English teaching [8][9][10].…”
Section: Introductionmentioning
confidence: 99%